2018
DOI: 10.1101/386805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shared genetic aetiology between cognitive performance and brain activations in language and math tasks

Abstract: Corresponding authors' information:Emails: yann.leguen@cea.fr (YLG), vincent.frouin@cea.fr (VF) 2 Cognitive performance is highly heritable. However, little is known about common genetic influences on cognitive ability and brain activation when engaged in a cognitive task. The Human Connectome Project (HCP) offers a unique opportunity to study this shared genetic etiology with an extended pedigree of 785 individuals. To investigate this common genetic origin, we took advantage of the HCP dataset, which include… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
(89 reference statements)
1
5
0
Order By: Relevance
“…Their results are close to our findings, since we also reduced dimensionality of our data and found 13 latent variables (out of 74 measures) and found heritability that ranged from 0.2 to 0.8. In-scanner task performance heritability estimates were also consistent with studies that used the same HCP data (Babajani-Feremi, 2017;Le Guen et al, 2018) .…”
Section: Heritability Of Brain Subtypes and Behavioral Measuresupporting
confidence: 77%
“…Their results are close to our findings, since we also reduced dimensionality of our data and found 13 latent variables (out of 74 measures) and found heritability that ranged from 0.2 to 0.8. In-scanner task performance heritability estimates were also consistent with studies that used the same HCP data (Babajani-Feremi, 2017;Le Guen et al, 2018) .…”
Section: Heritability Of Brain Subtypes and Behavioral Measuresupporting
confidence: 77%
“…Here we will focus on the quintessential and human-unique capacity for language. Previous studies have suggested that language-related cognitive performance is highly heritable (e.g., (Dale et al, 1998;Guen, Amalric, Pinel, Pallier, & Frouin, 2018;Newbury, Bishop, & Monaco, 2005)), and that brain activations associated with semantic comprehension tasks are also heritable (Guen et al, 2018). Moreover, genetic factors also play a substantial role in susceptibility to languagerelated neurodevelopmental disorders such as childhood apraxia of speech (Eising et al, 2018), developmental language disorder (specific language impairment) and developmental dyslexia (Deriziotis & Fisher, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic origin of language capacities 93 and other properties of hemispheric specialization reflect a fundamental question in cognitive neuroscience with clear relevance for the study of both health and disease 12 . Prior work indicates that intrinsic connectivity between language related regions 94 , as well as evoked brain activations during language tasks 95 , are heritable. Our present analyses indicate a clear genetic basis for population-level patterns of language lateralization and corresponding features of cortical organization.…”
Section: Discussionmentioning
confidence: 99%